(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The paper accentuation on composition protection originates from the reasonable issue of upkeep, care and conservation of the important legacy of India. The information on conservation isn’t new to Indians. Care of original copies was a main issue previously and endeavors were made to safeguard them from the various specialists of decay. An outline of protection and preservation technique of manuscripts in the libraries & information centre, One of the most significant of these decay specialists was natural development. The strategies used to save the original copies depended on experience and information on spices and other regular materials and these practices were passed down from one age to another. For a really long time caretakers of assortments in India have involved different normal materials for the conservation of their original copies. With the approach of this paper, advancements in the field of protection, and furthermore with the progressions in friendly and living frameworks the conventional practices and frameworks of preservation have tumbled to neglect. Mixed methods research is used to combines elements of quantitative research and qualitative research in order to research objectives and questions. The sources of relevant data can be optimized through the tools of data collection. The most frequently used data collection tools are observation, interview, questionnaire, case study, schedule etc. Simultaneously, notwithstanding the approach of reasonable synthetic compounds for protection, customary techniques for preservati on are practically speaking in a portion of the libraries and composition stores in India.